On Bindability - Breheny, Richard (Proceedings of the Amsterdam Colloquium, 2003)
Bindability is the ability of an expression to have its interpretation fixed relative to elements in a scopally superior quantificational expression's domain. There seems to be a bindability generalisation: if context-dependent, then bindable. Two better known accounts of context dependence and bindability are critically considered: the 'hidden variables' and 'presuppositional' approaches. A third account involving coercive lexical mechanisms in a variable-free framework will be offered. The 'bindability generalisation' will be reconsidered in the light of this proposal.